2002
DOI: 10.1207/s15327736me1503_3
|View full text |Cite
|
Sign up to set email alerts
|

Market Structure and Local Signal Carriage Decisions in the Cable Television Industry: Results From Count Analysis

Abstract: Using historical data collected by the U.S. General Accounting Office (GAO) in 1990 (GAO, 1990), a time when the must-carry rules were not in effect, this study empirically tested the effects of horizontal concentration, vertical integration, and other system-specific variables on cable operators' carriage decisions regarding local television stations. Results from the negative binomial regression model (a count model) indicate that horizontal concentration or firm size had a negative effect on cable system ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Above all, the findings of most previous studies have suggested that the size efficiency of MSOs does not increase consumer benefit (Clements & Brown, 2006;Emmons & Prager, 1997;Karikari, Brown, & Abramowitz, 2003;U.S. General Accounting Office, 2002Yan, 2002). To the contrary, the findings of other studies suggested that an increase in MSO size enhances consumer welfare (Ford & Jackson, 1997;Savage & Wirth, 2005).…”
Section: Previous Literature On the Implications Of Specific Charactementioning
confidence: 98%
“…Above all, the findings of most previous studies have suggested that the size efficiency of MSOs does not increase consumer benefit (Clements & Brown, 2006;Emmons & Prager, 1997;Karikari, Brown, & Abramowitz, 2003;U.S. General Accounting Office, 2002Yan, 2002). To the contrary, the findings of other studies suggested that an increase in MSO size enhances consumer welfare (Ford & Jackson, 1997;Savage & Wirth, 2005).…”
Section: Previous Literature On the Implications Of Specific Charactementioning
confidence: 98%
“…Most previous literature has investigated the implications of horizontal integration in the cable industry in terms of subscribers' welfare. The findings of most previous studies have suggested that the size efficiency of MSOs does not increase consumer benefit (Aufderheide, 1992;Clements and Brown, 2006;Emmons and Prager, 1997;Karikari et al, 2003;US GAO, 2002;Yan, 2002). For example, according to US GAO (2002), cable rates are higher when a cable system affiliates with one of the ten largest MSOs.…”
Section: Previous Literature On the Implications Of Horizontal Integration In The Cable Industrymentioning
confidence: 99%
“…Emmons and Prager (1997), using two-year cross-sectional data, examined the effects of ownership on the levels of rates and offerings of cable services in the USA and found that cable systems operated by MSOs have no significant impact on subscription rates and the number of channels for basic-tier-cable services. Yan (2002) investigated the effect of horizontal integration on cable operators' carriage decisions for local television stations and found that horizontal integration has a negative impact on these decisions. Interestingly, Aufderheide (1992) maintained that the US cable television industry provides consumers with a very limited diversity of sources and points-of-view on public issues and civic activism due to its market structure in which a few MSOs control half of the cable television market.…”
Section: Previous Literature On the Implications Of Horizontal Integrmentioning
confidence: 99%